Kesiapan Masyarakat Menerapkan Teknologi Tepat Guna Pengolahan Air Minum (Studi Kasus : Pulau Palu’e, Nusa Tenggara Timur) - Nugraha, Dimas Hastama; Mahida, Masmian (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Palu’e island region has no sources of fresh water for their daily consumption. In addressing such a need, the local community has used structural and cultural adaptation. They use these methods because of the quality of ground water is below the standard of quality as it is brackish, and is occasionally yellow. In practice, a lot of brackish water in the wells around people’s houses are only used for sanitary purposes. During the dry season the clean water is difficult to obtain especially the use of structural adaptation. In responding to such a problem the Center for Research and Development of Settlement has introduced processing technology for brackish/sea water into clean/fresh water which can can be readily consumed by the people of the island of Palu’e. Moreover, to ensure the sustainability of the operation of the technology, in terms of non-technical, Social Economic and Environment Research and Development Center implement community readiness mapping that includes individuals, community, and governance. In this paper, the author will be mapping of Palu’e community readiness in the applied technology of drinking water treatment. This study used descriptive qualitative-quantitative approach by analyzing the variables related to community readiness.The result from the mapping of community readiness indicate that the local community is ready in terms of individual, community and governance to implement technology of water processing. However the local people need to improve governance readiness because it shows the the lowest score compared with the individual and community readiness variables.